Critical Factors for Accounting Estimation of Investment in Artificial Intelligence: an Imperative for Accounting Standards Setters in the Fourth Industrial Revolution Era: Array - Salawu, Mary Kehinde; Moloi, Tankiso Steven (The Journal of Accounting and Management, 2020)
The major assets of the 21st century organisations have moved from the company premises to the cloud where the telescopic rules of accounting could not locate them. This study addressed the inadequacies of existing Accounting Principles and Standards in estimating Artificial Intelligence (AI) assets in the era of the fourth industrial revolution. Constant fusion of multiple technologies had substantially altered the nature of organizational non-current assets from tangible (physical) to intangible (non-physical). Assets considered as intangible by existing studies and accounting standards are largely goodwill, patents, trademarks, copyright, customer list etc while AI remains foreign to accounting valuation. The study employed desk-review to identify factors essential for policy review to accommodate further development in AI-accounting domain. The study found Intellectual property, increased investment AI assets, multi-functional savings, privacy infringement, ransoms and law suit among others as crucial for estimating AI assets in the 21st century. Estimating and reporting AI assets still domicile in an uninformative accounting environment. Therefore accounting practitioners, professional bodies, standard-setters, academics and researchers need to recognise and leverage its potential impacts on accounting education and organisational practices. The study concluded that AI assets should be capitalized using simple algorithm to promote the fairness of the financial reports.